THE EFFECT OF WORK ATTITUDE ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - Ramadhani, Melda Aulia; Rinaldi, Muhammad; Ariandi, Muhamad Amir (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
This study aims to examine the effect of work attitude on employee performance with organizational commitment as a mediating variable in private companies in Indonesia. The research is motivated by the growing importance of understanding psychological factors in human resource management, particularly in efforts to enhance employee performance. Employing a quantitative explanatory approach, the study collected data through a survey of 100 permanent employees. The findings reveal that work attitude has a positive and significant effect on employee performance, both directly and indirectly through organizational commitment as a mediating variable. Furthermore, work attitude significantly influences organizational commitment, which in turn positively affects employee performance. These findings highlight the importance of fostering a strong psychological connection between employees and their organization to improve work outcomes.